Resting‐state connectivity within and across neural circuits in anorexia nervosa. Issue 1 (27th December 2018) - Uniacke, Blair; Wang, Yun; Biezonski, Dominik; Sussman, Tamara; Lee, Seonjoo; Posner, Jonathan; Steinglass, Joanna
Abstract: Introduction: Obsessional thoughts and ritualized eating behaviors are characteristic of Anorexia Nervosa (AN), leading to the common suggestion that the illness shares neurobiology with obsessive–compulsive disorder (OCD). Resting‐state functional connectivity MRI (rs‐fcMRI) is a measure of functional neural architecture. This longitudinal study examined functional connectivity in AN within the limbic cortico‐striato‐thalamo‐cortical (CSTC) loop, as well as in the salience network, the default mode network, and the executive control network (components of the triple network model of psychopathology). Methods: Resting‐state functional connectivity MRI scans were collected in unmedicated female inpatients with AN ( n  = 25) and healthy controls (HC; n  = 24). Individuals with AN were scanned before and after weight restoration and followed for one month after hospital discharge. HC were scanned twice over the same timeframe. Results: Using a seed‐based correlation approach, individuals with AN had increased connectivity within the limbic CSTC loop when underweight, only. There was no significant association between limbic CSTC connectivity and obsessive–compulsive symptoms or prognosis. Exploratory analyses of functional network connectivity within the triple network model showed reduced connectivity between the salience network and left executive control network among AN relative to HC. These abnormalities persisted following weight restoration. Conclusions: The CSTC findings suggest that the neural underpinnings of obsessive–compulsive symptoms may differ from those of OCD. The inter‐network abnormalities warrant examination in relation to illness‐specific behaviors, namely abnormal eating behavior. This longitudinal study highlights the complexity of the neural underpinnings of AN. Abstract : Obsessional thoughts and ritualized eating behaviors are characteristic of Anorexia Nervosa (AN), leading to the common suggestion that the illness shares neurobiology with obsessive–compulsive disorder (OCD). Based on findings of abnormal limbic cortico‐striato‐thalamo‐cortical (CSTC) loop functional connectivity among individuals with OCD, this longitudinal study examined limbic CSTC functional connectivity in AN, as well as in the salience network, the default mode network, and the executive control network (components of the triple network model of psychopathology). There was no significant association between limbic CSTC connectivity and obsessive–compulsive symptoms or prognosis in AN; exploratory analyses of functional network connectivity within the triple network model showed weaker inter‐network connectivity among AN relative to HC between the salience network and left executive control network that persisted following weight restoration.